The Development of Android-Based Mobile Learning for Indonesian History Course at Vocational High School - Susila, Heni Rita; Isa, Yamanto; Wahidah, Nina Ikhwati (Edcomtech, 2023)
This study aimed to develop android-based mobile learning for Indonesian History course at SMK YIS Martapura. This is a Research and Development (R&D) using the Alessi & Trollip model.  Data collection techniques used questionnaire while research data were analyzed using the percentage formula. From the validation results, media experts scored got 88.69 percent belong to "Good" category. Instructional design experts scored is 82.0 percent which is belong to "Good" category. Material experts scored got 89.9 percent, belong to "Good" category. In one-to-one evaluation with the number of respondents is 3 students got an average result of 86.38 percent which is belong to "Very Good" category. Then a small group evaluation was carried out with 6 students as respondents got an average result of 86.73 percent belong to "Very Good" category. Furthermore, field test was carried out with a total of 28 students with an average result of 86.78 percent in the "Very Good" category. Field trial score showed that there is an increase of post-test. From the results of expert evaluations and field trials, it can be concluded that android-based mobile learning for Indonesian History subject at Vocational Schools show a good level of feasibility and can be accepted as one of the learning media that can be used in classroom learning.